Leukocyte telomere length and personality: associations with the Big Five and Type D personality traits. Issue 6 (11th September 2017) - Schoormans, D.; Verhoeven, J. E.; Denollet, J.; van de Poll-Franse, L.; Penninx, B. W. J. H.
Abstract : Backgrounds: Accelerated cellular ageing, which can be examined by telomere length (TL), may be an overarching mechanism underlying the association between personality and adverse health outcomes. This 6-year longitudinal study examined the relation between personality and leukocyte telomere length (LTL) across time among adults with a wide age-range. Methods: Data from the Netherlands Study of Depression and Anxiety were used and included patients with a depression and/or anxiety disorder and healthy controls. Overall, 2936 persons (18–65 years, 66% female) had data on LTL at baseline and 1883 persons had LTL at 6-year follow-up. The Big Five personality traits (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) and Type D personality were assessed. Results: Neuroticism was negatively ( B = −2.11, p = 0.03) and agreeableness was positively ( B = 3.84, p = 0.03) related to LTL measured across two time points, which became just non-significant after adjusting for somatic health, lifestyle factors, and recent life stress ( B = −1.99, p = 0.06; and B = 3.01, p = 0.10). Type D personality was negatively ( B = −50.16, p < 0.01) related to LTL across two time points, which still remained statistically significant after full adjustment ( B = −47.37, p = 0.01). Associations did not differ by age, gender, and current psychiatric status. Conclusions: The Big Five traits high neuroticism and low agreeableness, and Type D personality were associated with shorter LTL measured across a 6-year period. Associations with the Big Five traits became non-significant after controlling for somatic health, lifestyle factors, and recent life stress, yet similar trends were observed. Type D personality remained independently associated with shorter LTL after full adjustment.